ENGLISH TEACHERS’ PERCEPTION IN DESIGNING WRITING TECHNIQUES TO IMPROVE STUDENTS’ WRITING ABILITY - Ayudhia, Honesty Yonanda (Proceedings Education and Language International Conference, 2017)
Teaching writing in senior high school is one of an interesting issue since teachers see writing as one of the hardest skill to teach. Some consideration is needed in teaching writing. Since teachers are the important aspect in writing class, this paper will examine senior high school teachers' perception in designing writing techniques that can help the students in improving their writing ability. The techniques will be measured based on some principles that are adapted from Brown (2001). There will be 30 teachers from all of the English teachers in Indonesia that were taken as participants of this research. These participants would be taken by using random sampling technique. The instrument of this descriptive research was set of close ended and open ended questionnaire. The result of this research showed that teachers' have positive perception on designing writing techniques but it needs some changes in its practice in the classroom.Keywords: teachers’ perception, techniques, writing ability